Anodization of Electrodeposited Titanium Films Towards TiO2 Nanotube Layers - Sopha, Hanna; NORIKAWA, Yutaro; Motola, Martin; Hromádko, Luděk; Rodriguez Pereira, Jhonatan; Černý, Jiří; Nohira, Toshiyuki; Yasuda, Kouji; Macák, Jan (Elsevier, 2020)
Ti films, electrodeposited on Ni foils from molten salts, were anodized towards TiO2 nanotube formation for the first time. The resulting TiO2 nanotube (TNT) layers were compared with TNT layers prepared under identical conditions on Ti foils by means of scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements, X-ray photoelectron spectroscopy (XPS), and photocurrent measurements. No significant differences can be found for the TNT layers prepared on the two different substrates. As-electrodeposited Ti films could be a viable candidate for anodization purposes.
Keywords: TiO2; nanotubes; electrodeposited Ti; anodization; photoelectrochemistry